Primary and secondary metabolite compounds in cowpea seeds resistant to the cowpea bruchid [Callosobruchus maculatus (F.)] in postharvest storage. (September 2021) - Kpoviessi, Akovognon Dieudonné; Agbahoungba, Symphorien; Agoyi, Eric E.; Nuwamanya, Ephraim; Assogbadjo, Achille E.; Chougourou, Daniel C.; Adoukonou-Sagbadja, Hubert
Abstract: Cowpea is a one important legume crop in Sub-Saharan Africa due to its high content of protein and other nutrients. However, seeds of cowpea varieties are destroyed by Callosobruchus maculatus in storage. This study investigated various biochemical compounds of susceptible and resistant cowpea genotypes, to determine the biochemical compounds underlying cowpea resistance to bruchid. Six cowpea genotypes were analyzed in three replicates. One-way analysis of variance, Pearson correlation and path analysis were used to determine the influence of the biochemical compounds on the cowpea status. Amongst the cowpea genotypes assayed the biochemical compounds analyzed (Vicilin; α-amylase Inhibitor; Phenols; Condensed Tannin; Tannin; Carbohydrate; Flavonoid and Protein), were present in amounts. Resistant genotypes exhibited higher contents of Phenols (22.29 mg/g for WC66*5T and 19.74 mg/g for WC36); Tannin (2.45CEmg/g for WC36 and 2.52CEmg/g for TVU13677); and Carbohydrate (72.82% for TVU13677 and 71.09% for WC36). The most susceptible genotypes had the lowest content of Phenols (13.5 mg/g for TVU946 and 12.72 mg/g for Glessissaffodo); Tannin (0.74CEmg/g for Akounado and 0.97CEmg/g for Glessissaffodo) and Carbohydrate (60.95% for Akounado and 61.39% for TVU946), while Condensed Tannin was associated to their seed coat colour but not to their resistance status against bruchid. The resistant genotypes TVU13677; WC36 and WC66*5T were found to contain a higher amount of a subset of biochemical compounds as defensive compounds against cowpea bruchid. The susceptible cowpea genotypes (Akounado; Glessissaffodo; TVU946) screened for their biochemical content presented low amounts of these defensive compounds. The path analysis implemented highlighted the existence of causal relationships among biochemical compounds analyzed and resistance parameters, thus revealing the resistance basis of cowpea seed biochemical compounds. These latter results point out the possibilities to consider the presence of these biochemical compounds underlying the resistance of cowpea to bruchid in the breeding program toward the resistance to bruchid. Highlights: Cowpea is an important legume crop due to its high content of nutrients. Cowpea bruchid is the most destructive pest of cowpea in storage. Presence in cowpea seed of biochemical compounds resistant to bruchid. Existence of causal relationships among parameters based on the path analysis. Promising cowpea biochemical compounds for the bruchid-resistant breeding program.